(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Sydorenko T. D. Ukrainian musical folklore as a source of traditional pedagogy. The article proves the expediency of using during the music lessons in the secondary school the Ukrainian folk music, which creates a pupil’s conditions for the involvement of spiritual values, offering in different life situations rich variety of experiences musical experience.